Molecular Detection of Candida auris Using DiaSorin Molecular Simplexa® Detection Kit (2023)
Candida auris is a globally emerging fungal pathogen that is associated with healthcare-related infections. The accurate and rapid detection of C. auris is crucial for effective infection prevention, control, and patient management. This study aimed to validate the analytical and diagnostic performance of the DiaSorin Molecular C. auris Detection Kit. The analytical specificity, sensitivity, and reproducibility of the assay were evaluated. The limit of detection (LOD) was determined to be 266 CFU/µL using the ZeptoMetrix Candida auris Z485 strain and standard calibration curves. The assay demonstrated high analytical specificity and showed no amplification against a diverse panel of bacteria and fungi. Clinical validation was conducted using deidentified residual axillary/groin surveillance culture specimens from C. auris culture-positive and culture-negative patients. The DiaSorin Molecular Detection Kit exhibited 100% agreement in sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) when compared to cultures coupled with MALDI-TOF identification. Intra- and inter-reproducibility testing demonstrated consistent and reliable diagnostic performance. This validated assay offers rapid and accurate detection of C. auris, facilitating timely implementation of infection control measures and appropriate patient care. The DiaSorin Molecular C. auris Detection Kit has the potential to aid in controlling the outbreaks caused by this emerging fungal pathogen. Providing a reliable diagnostic tool can contribute to the effective management and containment of C. auris infections in healthcare settings and ultimately improve patient outcomes.